1982
DOI: 10.1084/jem.155.6.1823
|View full text |Cite
|
Sign up to set email alerts
|

Lymphokine-activated killer cell phenomenon. Lysis of natural killer-resistant fresh solid tumor cells by interleukin 2-activated autologous human peripheral blood lymphocytes.

Abstract: Activation in lectin-free interleukin 2 (IL-2) containing supernatants of peripheral blood mononuclear leukocytes (PBL) from cancer patients or normal individuals resulted in expression of cytotoxicity toward 20 of 21 natural killer (NK)-resistant fresh solid tumor cells tested. Fresh solid tumor cells were resistant to NK-mediated lysis in 10 autologous patients' PBL-tumor interactions, and from 17 normal individuals tested against 13 allogeneic fresh tumors. Culture of PBL in IL-2 for 2-3 d was required for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
629
2
7

Year Published

1989
1989
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,009 publications
(658 citation statements)
references
References 31 publications
13
629
2
7
Order By: Relevance
“…Both CD3 − and CD3 + LAK cells show non-MHC-restricted specificity. 12,13 While the molecular basis of tumor cell recognition by these effector cell types remains to be defined it has been found that the adhesion molecules ICAM-1 (CD54) and leukocyte-associated function molecule 3 (LFA-3, CD58) are important for optimal effector-target cell interactions. [14][15][16] More rarely, classical MHC-restricted CTL have been identified in RCC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Both CD3 − and CD3 + LAK cells show non-MHC-restricted specificity. 12,13 While the molecular basis of tumor cell recognition by these effector cell types remains to be defined it has been found that the adhesion molecules ICAM-1 (CD54) and leukocyte-associated function molecule 3 (LFA-3, CD58) are important for optimal effector-target cell interactions. [14][15][16] More rarely, classical MHC-restricted CTL have been identified in RCC patients.…”
Section: Introductionmentioning
confidence: 99%
“…It is established that certain lymphocytes cultured in the presence of IL-2 develop into an activated natural killer cell phenotype (lymphokine activated killer cells; LAK cells) with enhanced cytotoxic activity against malignant target cells [1][2][3][4]. There are numerous clinical attempts based on adoptive immunotherapy (AIT) of cancer disease with various subsets of LAK cells [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Any form of chemotherapy, immunotherapy or hormone therapy had to be discontinued 6 weeks before blood collection. After removal of the adherent monocytes by incubating the PBMCs on plastic plates for 1 h at 37C, the PBLs were decanted and either cryopreserved or immediately processed for the generation of LAK cells (Grimm et al, 1982;Schadendorf et al, 1994b). In short, PBLs were incubated at a density of 2 x 106 cells ml-' in RPMI-1640 supplemented with glutamine, fetal calf serum and antibiotics as mentioned above, and 1,000 U ml1' IL-7 or 100 U ml1' IL-2.…”
Section: Cvtokinesmentioning
confidence: 99%